Geriatric Assessment Is Associated With Reduced Mortality at 1 Year for Older Adults Admitted to a Major Trauma Center: A Prospective Observational Study. Issue 2 (10th February 2023) - Ibitoye, Sarah E.; Braude, Philip; Carter, Ben; Rickard, Frances; Deakin, Helen; Martin, Rebecca; Thompson, Julian; Walton, Benjamin; Shipway, David
Abstract : Objective: To evaluate the effect of geriatrician review on 1-year mortality in older adults admitted with trauma. Background: Comprehensive geriatric assessment (CGA) has been associated with improved outcomes in older adults with hip fracture, but has not been evaluated in a broader trauma population. Methods: Trauma patients aged ≥ 65years admitted to an English Major Trauma Centre between November 2018 and September 2019 were included. Patients were divided into 3 cohorts: no geriatric assessment, reactive geriatric assessment, and proactive CGA. The primary outcome was time to mortality, secondary outcomes were time to discharge and frequency of complications. Analyses were adjusted for factors known to be associated with outcomes including age, frailty, injury severity, and complications. Results: Five hundred eighty-five patients were included (no geriatric assessment = 125; reactive geriatric assessment = 134; proactive CGA = 326): median age was 81 years (IQR 74-88); 326 (55.7%) were women; 297 (50.8%) were living with frailty (Clinical Frailty Scale ≥5). Median Injury Severity Score was 13 (IQR9-25). At 1-year follow-up, 147 (25.1%) patients had died. In multivariate analysis, both types of geriatric assessment were associated with reduced mortality [reactive aHR = 0.31, 95% CI 0.18–0.53; proactive adjusted hazard ratio (aHR) = 0.41, 95% CI 0.26–0.64]. There was no association between either type of geriatric assessment and length of stay (reactive aHR = 0.84, 95% CI 0.62–1.15; proactive aHR = 0.80, 95% CI 0.63–1.02). Conclusions: Geriatrician assessment is associated with reduced mortality in older adults admitted following trauma. Further research should focus on defining optimal models of geriatrician intervention.